2004
DOI: 10.1111/j.1460-9592.2004.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed rises in serum S100B levels and adverse neurological outcome in infants and children undergoing cardiopulmonary bypass

Abstract: The results of this study suggest that monitoring S100B levels in the late postoperative period may still have a role in detecting neurological injury after cardiac surgery in children. Consistent with previous observations, S100B is high preoperatively in neonates and early postbypass in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
0
25
0
4
Order By: Relevance
“…Serum S100b can detect early brain injury, 11,29 change in response to secondary brain insults 30 , and predict outcome after various adult and pediatric CNS injuries 18,29,3134 . Berger et al found that initial and peak serum S100b concentrations were increased in children with hypoxic-ischemic injury and traumatic brain injury (TBI) but children with TBI peaked earlier (6 vs. 9 hours) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum S100b can detect early brain injury, 11,29 change in response to secondary brain insults 30 , and predict outcome after various adult and pediatric CNS injuries 18,29,3134 . Berger et al found that initial and peak serum S100b concentrations were increased in children with hypoxic-ischemic injury and traumatic brain injury (TBI) but children with TBI peaked earlier (6 vs. 9 hours) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Lardner et al reported data from 43 children undergoing surgery with CPB. (27) Neonates had elevated S100β levels preoperatively, and all patients had elevated levels immediately postbypass. There was no association between elevated S100β levels 24 hr after bypass and outcomes; however in the two patients with acute neurological injury and later developmental delay, the increase at 48 hr was significantly higher than the remaining patients without brain injury.…”
Section: Markers/surrogates For Neurological Injurymentioning
confidence: 89%
“…Increased S-100B levels correlate with the presence of brain infarction, and the extent of infarcted brain tissue. S-100B has been shown to predict survival, long-term outcome, degree of postoperative neurological deficit and intellectual impairment [131][132][133][134][135][136]. Moreover, Kanbak et al used serum S-100B in order to show that propofol offers no advantage over isoflurane anaesthesia for cerebral protection during cardio-pulmonary bypass [137].…”
Section: Stroke-cerebral Hypoxiamentioning
confidence: 99%